1998
DOI: 10.3141/1617-04
|View full text |Cite
|
Sign up to set email alerts
|

Trip Generation and Parking Requirements in Traditional Shopping Districts

Abstract: The New Urbanists assume that if you build a village center or Main Street-style retail businesses in the middle of a residential neighborhood, it will, among other things, reduce the level of automobile usage. Based on the claim of reduced automobile travel, advocates suggest that parking requirements and transportation impact fees should similarly be reduced. Although it would be ideal to test these claims using New Urbanist development, current developments lack well-established retail businesses. Thus, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Research has also shown that people trade off convenience with price, quality, parking availability, and other intangibles when grocery shopping (Handy and Clifton, 2001). An empirical investigation of traditional shopping districts found that while these districts are associated with higher rates of walking, bicycling and transit, many people still access them by car, especially if visiting grocery stores (Steiner, 1998). Results of these studies have suggested and supported the notion that driving to supermarkets is attractive compared with other travel modes due to the ease of transporting grocery bags.…”
Section: Supermarket Spendingmentioning
confidence: 48%
“…Research has also shown that people trade off convenience with price, quality, parking availability, and other intangibles when grocery shopping (Handy and Clifton, 2001). An empirical investigation of traditional shopping districts found that while these districts are associated with higher rates of walking, bicycling and transit, many people still access them by car, especially if visiting grocery stores (Steiner, 1998). Results of these studies have suggested and supported the notion that driving to supermarkets is attractive compared with other travel modes due to the ease of transporting grocery bags.…”
Section: Supermarket Spendingmentioning
confidence: 48%
“…Intercept surveys are useful for gathering a sufficient sample of trips associated with specific activity centers. Intercept surveys can be used to gather sufficient data about travel to specific activity locations, such as shopping districts (Steiner 1998), transit hubs (Schaller 2005), and multi-use trails (Krizek et al 2007). Household travel surveys often capture a representative sample of people in residential neighborhoods, but they may not provide sufficient data for documenting trips to, from, and within particular activity centers.…”
Section: Introductionmentioning
confidence: 99%
“…1016/j.ejor.2005.02.033 strategy. During the last four decades numerous parking search models have been developed (Van der Goot, 1982;Axhausen and Polak, 1991;Polak and Axhausen, 1990;Young et al, 1991a,b;Saltzman, 1997;Shoup, 1997;Steiner, 1998;Thompson and Richardson, 1998;Arnott and Rowse, 1999;Tam and Lam, 2000;Wong et al, 2000;Waterson et al, 2001). In many decision-making situations in transportation (modal split, choice of air carrier, choice of airport, etc.)…”
Section: Introductionmentioning
confidence: 98%